EVALUATION OF AROMATERAPIC LILIN AIDE FORMULATION FROM AGRICULTURAL OIL OF AURISH (Cymbopogon citratus) AS AROMATERAPIC RELAXANT AND INSECT REPELLENT - Hutahaen, Titi Agni; Nirmala, Atika; Nisa, Khoirotun; Saradewi, Amelya (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
This study aimed to evaluate the formulation of aromatherapy candles using citronella essential oil (Cymbopogon citratus) as the active ingredient. Lemongrass essential oil was chosen because it has two main functions: as an aromatherapeutic relaxant and as an insect repellent. In this study, several candle formulations were prepared with varying concentrations of essential oils to determine the most effective and stable formulation. An effectiveness test was conducted by measuring the intensity of the scent, burning duration of the candle, and the ability to repel insects. The results showed that candles with 25% essential oil provided the best balance between scent intensity and insect repellent effectiveness. The candles also exhibited good stability during the storage. In conclusion, kitchen lemongrass essential oil is a potential ingredient for use in aromatherapy candles that not only provides a relaxing effect, but also functions as a natural insect repellent.  Keywords: kitchen lemongrass, aromatherapy candles, relaxants, insect repellent